Factors Associated with Nurses’ Attitudes Towards Evidence- Based Practice in Turkey - ULAŞ KARAAHMETOĞLU, Gülşen; KUTAHYALİOGLU, Nesibe; NARAYAN, Mary (Marmara University, 2022)
Objective: Nurses’ attitudes related to Evidence-Based Practices (EBP) have been widely studied in Western countries, on the other hand, few studies have examined nurse attitudes and practices related to evidence-based practice in Eastern European and Middle Eastern countries. Therefore, we investigated Turkish nurses’ attitudes towards evidence-based practice and the socio-demographic factors associated with it in Turkey. Methods: This is a descriptive study using a sample of 290 nurses employed by three hospitals in Turkey. Participants completed the Evidence- Based Nursing Attitude Questionnaire and a demographic survey to measure 13 personal, occupational, and professional variables. The analysis included descriptive statistics, t-tests, and ANOVA. Results: The results of the study showed that nursing education, ability to use professional nursing standards, and conference attendance were significantly associated with higher evidence-based practice. Nurses who had a membership in a professional organization reported higher scores in the cognitive subscale. Younger nurses who have least length of nursing experience stated higher scores in the affective subscale. Moreover, nurses who use professional nursing standards in practice told higher scores in the behavioral subscale. Conclusion: There are several factors associated with greater evidence-based practice among nurses, those are identified as higher nursing education, professional organization membership, conference attendance, and more satisfaction with income. Results suggest providing inservice education for older and experienced nurses in the benefits and processes of evidence-based practice, supporting activities that promote professionalism.
Keywords: Health Care Administration; evidence-based practice; evidence-based nursing; nurse attitudes; professional nursing practice; nursing; Turkey.; Sağlık Kurumları Yönetimi; 3. Good health